ANALISIS FILOSOFIS-KRITIS FENOMENA SOUND HOREG DALAM BINGKAI HUKUM ISLAM DAN KEARIFAN LOKAL - Ahmad Mu'is; Sawaluddin Siregar; Rosyida Nurul Anwar; Andrian Khoirul Ummah (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2025)
The phenomenon of sound horeg, which is the use of high-powered audio equipment in various community activities, has sparked debate between entertainment values, public order, and religious norms. This study aims to analyze sound horeg from an Islamic legal perspective using a philosophical-critical approach, while also considering the role of local wisdom as an instrument of social regulation. The research method used is field research with in-depth interviews, participatory observation, and documentary studies of entertainment practitioners, religious leaders, village officials, and affected residents. Data analysis is conducted qualitatively using a hermeneutic-philosophical approach to interpret the relationship between the principles of maqashid syariah, customary norms, and contemporary cultural practices. The results of the study indicate that sound horeg is acceptable under Islamic law as long as it fulfills the principle of maslahah (public interest), does not cause harm, and respects the public's right to peace and quiet. Local wisdom functions as a mechanism for adapting values, but its effectiveness depends on social consensus and the moral commitment of the community. This study recommends a community-based regulatory model that is in line with Sharia and cultural values, in order to create a balance between freedom of expression in entertainment and public order.